Lipid A structural diversity among members of the genus Leptospira - Pětrošová, Helena; Mikhael, Abanoub; Culos, Sophie; Giraud-Gatineau, Alexandre; Gomez, Alloysius M.; Sherman, Matthew E.; Ernst, Robert K.; Cameron, Caroline E.; Picardeau, Mathieu; Goodlett, David R. (Frontiers in Microbiology, 2023)
Lipid A is the hydrophobic component of bacterial lipopolysaccharide and an activator of the host immune system. Bacteria modify their lipid A structure to adapt to the surrounding environment and, in some cases, to evade recognition by host immune cells. In this study, lipid A structural diversity within the Leptospira genus was explored. The individual Leptospira species have dramatically different pathogenic potential that ranges from non-infectious to life-threatening disease (leptospirosis). Ten distinct lipid A profiles, denoted L1-L10, were discovered across 31 Leptospira reference species, laying a foundation for lipid A-based molecular typing. Tandem MS analysis revealed structural features of Leptospira membrane lipids that might alter recognition of its lipid A by the host innate immune receptors. Results of this study will aid development of strategies to improve diagnosis and surveillance of leptospirosis, as well as guide functional studies on Leptospira lipid A activity.